Sedimentology and stratigraphy of deep-water reservoirs in the 9A to 14A Sequences of the central Bredasdorp Basin, offshore South Africa - Megner-Allogo, Alain-Cedrique (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--University of Stellenbosch, 2006.